2013
DOI: 10.1080/09084282.2011.643964
|View full text |Cite
|
Sign up to set email alerts
|

Does Rey Complex Figure Copy Performance Measure Executive Function in Children?

Abstract: The Rey Complex Figure Task (RCFT) is currently utilized with both adult and child clinical populations. In addition to the measurement of visual-constructional ability and memory, the RCFT has also been suggested as a measure of executive function (EF), specifically requiring planning and organizing skills. The purpose of the current study was to determine the extent to which the RCFT Copy task, using the scoring system developed by Meyers and Meyers (1995), tapped components of EF. The participants in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 34 publications
3
9
1
Order By: Relevance
“…Results of forward regression showed that the strongest predictor of depression was recall on Rey-Osterrieth test, measuring primarily visuospatial memory with some elements of planning and organizing, followed by performance on Stroop test, one of the measures of executive functioning, especially inhibitory control and cognitive flexibility. Namely, in addition to the measurement of visual-constructional ability and memory, the ROCF has been suggested as a measure of executive function, specifically requiring planning and organizing skills (Elderkin-Thompson et al, 2004;Weber, Riccio, & Cohen, 2013). Several of our findings are in line with previous reports demonstrating that there is a strong negative correlation between depression in older adults and executive functioning (e.g., higher depression is indicative of impaired executive functioning).…”
Section: Discussionsupporting
confidence: 90%
“…Results of forward regression showed that the strongest predictor of depression was recall on Rey-Osterrieth test, measuring primarily visuospatial memory with some elements of planning and organizing, followed by performance on Stroop test, one of the measures of executive functioning, especially inhibitory control and cognitive flexibility. Namely, in addition to the measurement of visual-constructional ability and memory, the ROCF has been suggested as a measure of executive function, specifically requiring planning and organizing skills (Elderkin-Thompson et al, 2004;Weber, Riccio, & Cohen, 2013). Several of our findings are in line with previous reports demonstrating that there is a strong negative correlation between depression in older adults and executive functioning (e.g., higher depression is indicative of impaired executive functioning).…”
Section: Discussionsupporting
confidence: 90%
“…A deficit in "higher-order" functions such as planning or visual attention could explain this kind of poor ROCF copy results [7,29,30]. However, we have not found Attention (e.g.…”
Section: Discussioncontrasting
confidence: 66%
“…For the recall conditions, Shorr, Delis and Massman (1992) believe that the prefrontal cortex guides the ROCF task, as frontal lobe processes strategically encode, retrieve and store visuo-spatial information. Weber et al (2013) add that evidence from reduced ROCF performance in individuals with neuropsychological conditions reflects the number of executive function processes linked to the task.…”
Section: The Rey-osterrieth Complex Figure (Rocf) and Autism/adhdmentioning
confidence: 89%